Multifocal brain abscesses caused by invasive Streptococcus intermedia: A case report - Yao, Lin; Chen, Sansong; Yu, Zuan; Yu, Tao (Frontiers in Neurology, 2022)
Multifocal brain abscesses caused by invasive Streptococcus intermedia are relatively rare. Here, we present a 67-year-old male was admitted to the hospital for unconsciousness and fever. The computed tomography (CT) examination showed multiple intracranial space-occupying and “cavity-like” changes in the right lower lung. The examination of cerebrospinal fluid (CSF) was consistent with typical bacterial meningitis, CSF analyses revealed leukocytosis (10300  106 /L), elevated protein levels (140.39 mg/dL), decreased glucose levels (0.27 mmol/L), and normal chloride concentration level (120.2 mmol/L), however, pathogens were not detected in the cultures. Then, the CSF and sputum samples were analyzed using meta-genomic next-generation sequencing (mNGS), and S. intermedia was detected in both samples. We adjusted the use of antibiotics according to the results of mNGS in time. After anti-infective treatment, the patient achieved good treatment results in a very short time. This case highlights the mNGS can identify pathogens of brain abscess, and provide strong evidence for clinical diagnosis and treatment strategy.